The consequences of poaching and anthropogenic change for forest elephants. Issue 5 (7th April 2016) - Breuer, Thomas; Maisels, Fiona; Fishlock, Vicki
Abstract: Poaching has devastated forest elephant populations (Loxodonta cyclotis), and their habitat is dramatically changing. The long‐term effects of poaching and other anthropogenic threats have been well studied in savannah elephants (Loxodonta africana), but the impacts of these changes for Central Africa's forest elephants have not been discussed. We examined potential repercussions of these threats and the related consequences for forest elephants in Central Africa by summarizing the lessons learned from savannah elephants and small forest elephant populations in West Africa. Forest elephant social organization is less known than the social organization of savannah elephants, but the close evolutionary history of these species suggests that they will respond to anthropogenic threats in broadly similar ways. The loss of older, experienced individuals in an elephant population disrupts ecological, social, and population parameters. Severe reduction of elephant abundance within Central Africa's forests can alter plant communities and ecosystem functions. Poaching, habitat alterations, and human population increase are probably compressing forest elephants into protected areas and increasing human–elephant conflict, which negatively affects their conservation. We encourage conservationists to look beyond documenting forest elephant population decline and address the causes of these declines when developing conversation strategies. We suggest assessing the effectiveness of the existing protected‐area networks for landscape connectivity in light of current industrial and infrastructure development. Longitudinal assessments of the effects of landscape changes on forest elephant sociality and behavior are also needed. Finally, lessons learned from West African elephant population loss and habitat fragmentation should be used to inform strategies for land‐use planning and managing human–elephant interactions.